Population pharmacokinetic study of pemetrexed in chinese primary advanced non-small cell lung carcinoma patients - Cao, Peng; Guo, Wei; Wang, Jun; Wu, Sanlan; Huang, Yifei; Wang, Yang; Liu, Yani; Zhang, Yu (Frontiers in Pharmacology, 2022)
The purposes of this study were to identify physiological and genetic factors that contributed to variability of pemetrexed exposure and to optimize the dosing regimens for Chinese non-small cell lung carcinoma patients. A prospective population pharmacokinetics (PPK) research was performed in this population. The PEM concentrations of 192 plasma samples from 116 in-hospital patients were detected. All patients were genotyped for polymorphisms. The PPK model of PEM was developed. The pharmacokinetic behavior of PEM was described by a two-compartment model with first-order elimination. The population typical values were as follows: clearance (CL) 8.29 L/h, intercompartmental clearance (Q) 0.10L/h, central volume of distribution (V1) 18.94 L and peripheral volume of distribution (V2) 5.12 L. Creatinine clearance (CrCl) was identified as a covariate to CL, and ERCC1 (rs3212986) and CYP3A5 (rs776746) gene polymorphisms as covariates to Q. By using empirical body surface area (BSA)-based dosing strategy, PEM exposure decreased with the elevation of CrCl. Contrarily, CrCl-based dosing strategy exhibited a satisfactory efficacy of achieving the target PEM exposure. BSA-based dosing regimen in current clinic practice is not suitable to achieve the target exposure in PEM chemotherapy of Chinese NSCLC patients. Alternatively, renal function-based dosing strategy is suggested.